ICARE Model (Introduction, Connection, Application, Reflection, Extension) in Physics Learning: Analysis of its Effect on Students’ Computational Thinking Skills based on Gender - Latifah, Sri; Diani, Rahma; Malik, Safira Lusiana Marinda (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This study aims to determine the effect of the ICARE learning model on students’ computational thinking skills, the effect of gender differences on students’ computational thinking skills, and the interaction between the ICARE learning model and gender differences in students’ computational thinking. The research method used is quasi-experimental. This research was conducted at high school, SMA Muhammadiyah Bandar Lampung. The population in this study is class X MIPA with a sample of X MIPA 1 and X MIPA 3. The sampling technique is cluster random sampling. Hypothesis testing using a two-way ANOVA test with a 2x2 factorial design. The results of this study are: 1) there is an effect of the ICARE learning model on students’ computational thinking skills, with a significance level of 0.000 <0.05, 2) there is no effect of gender differences on computational thinking skills, with a significance level of 0.628 > 0.05, and 3) there is no interaction between ICARE learning models and gender differences on computational thinking skills, with a significance of 0.320> 0.05. Problem-solving in physics learning can use computational thinking skills, namely by indicators of decomposition, abstraction, algorithms, and generalization of patterns. So that, computational thinking skills are important in the physics learning process.